La détention provisoire au Québec : une pratique judiciaire courante - Garceau, Marie-Luce (Criminologie, 1990)
Little is known in Québec about detention before sentencing also known as provisionnel detention. This is a study of the population admitted to provisionnel detention between 1981 and 1985. The author presents the conceptual framework in which this study was undertaken and, with the help of statistical data, she draws a portrait of the population concerned. The author points out there is a disparity between the theory and practice of provisionnel detention. Furthermore, it is used disproportionately for marginal groups of detained persons.